2011
DOI: 10.1002/jmri.22788
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related cerebral perfusion changes in the parietal and temporal lobes measured by pulsed arterial spin labeling

Abstract: Purpose: To investigate age-related regional perfusion changes focused on the medial temporal lobes and related parietal areas using a pulsed arterial spin labeling technique. Materials and Methods:Resting cerebral blood flow (CBF) maps were obtained from 44 healthy volunteers (18 male, 26 female; age range, 19 to 79 years) using a pulsed arterial spin labeling (PASL) MRI technique at 3 Tesla focused on the parietal and temporal lobes. Repeated measurements were performed in 20 subjects to assure the reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 38 publications
10
36
1
Order By: Relevance
“…Elderly volunteers showed reduced baseline CBF in different brain regions. These results are in agreement with previous studies using ASL methods (4,22,23,25,32,33). Although some studies reported no CBF differences with advanced age (4,24), Liu et al (22) established that CBF is diminished in elderly even when accounting for major confounding effects from vascular alterations.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Elderly volunteers showed reduced baseline CBF in different brain regions. These results are in agreement with previous studies using ASL methods (4,22,23,25,32,33). Although some studies reported no CBF differences with advanced age (4,24), Liu et al (22) established that CBF is diminished in elderly even when accounting for major confounding effects from vascular alterations.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with previous studies using ASL methods (4,22,23,25,32,33). Although some studies reported no CBF differences with advanced age (4,24), Liu et al (22) established that CBF is diminished in elderly even when accounting for major confounding effects from vascular alterations. Moreover, the CBF decrease in the elderly has been associated with degenerative changes in microvasculature (33) and linked with subcortical white matter health (23), which may have implications for the mechanisms of neurodegeneration (34).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…[10] and [11]) was modified to use a single 90 flip angle readout instead of multiple low-flip angle readouts (i.e., using T 1 instead of T 1e ). Typical PASL sequences use bolus saturation from 700 ms up to between 1200 and 1600 ms (32)(33)(34)(35) and with TI ranging from 1400 to 1800 ms. For our simulations, we have chosen a bolus saturation start at 700 ms, a bolus saturation end at 1200, 1400, and 1600 ms, and an TI of 1700 ms. The measured GM mean T 1 , k A , k B over all patients were used to simulate the perfusion weighted signal DM .…”
Section: Validationmentioning
confidence: 99%